Temporal patterns of subjective experiences and self-regulation during Ramadan fasting among elite archers: A qualitative analysis - Roy, J.; Hamidan, S.; Singh, R. (Asian Journal of Sports Medicine, 2011)
Purpose: Some major competitions (e.g.London Olympics,2012) are scheduled during the Ramadan fasting month. Little attention has been given to explore the archers' performance related subjective experiences with a qualitative method. Therefore, this study addressed individual archers' subjective experiences within the framework of self-regulation during Ramadan. Methods: Eleven elite Malaysian Muslim fasting archers volunteered to participate in the study. Grounded theory was the qualitative approach used to examine the subjective experiences of athletes during Ramadan. Interviews were conducted and inductive content analysis was adopted to identify the temporal patterns of self-regulation of subjective experiences across the fasting period. Results: Inductive content analysis identified (a) physical, (b) mental,(c) emotional, (d) behavioral, and (e) spiritual experiences. Overall patterns revealed that experiences associated with physical, emotional, behavioral, and spiritual dimensions dominated in the first phase of fasting, while the mental dimension surfaced increasingly in the latter phase of fasting. Conclusions: The trend showed changes in the patterns of experiences among the major domains across the temporal dimension. Athletes reported increased subjective experiences in mental factors toward the latter half of the fasting period. Practitioners should emphasize on mental aspects of training, as these appear to be salient in archery performance.